Optimized condition for pei-based transient transfection of lifeact-gfp/nls-mcherry expressing plasmid used as cell barcode for syncytia live cell imaging - Kumara, Dennaya; Harsan, Hayfa Salsabila; Novianti, Metta; Lestari, Dinda; Septisetyani, Endah Puji; Prasetyaningrum, Pekik Wiji; Paramitasari, Komang Alit; Meiyanto, Edy (Jurnal Teknosains, 2023)
The transfection efficiency positively affects the successful plasmid DNA transfer into cells, with the highlight on the amount of plasmid DNA and its ratio to the transfection reagent. Polyethyleneimine (PEI) is a cost-effective transfection reagent that facilitates DNA transfer by forming positively charged DNA complexes. It allows DNA to interact with negatively charged cell surfaces and enter the cells by endocytosis. In this study, we optimized the condition for transient transfection of life act-GFP/NLS-mCherry-expressing plasmid in BHK-21 and 293T cells using PEI. This plasmid is helpful as a biosensor of the cytoskeleton and nucleus that enables live imaging observation using a fluorescence microscope, for instance, in the observation of syncytium. Here, we optimized two independent variables: the amount of DNA (0.5 and 1 µg) and the ratio of DNA-PEI (1:3 and 1:4). GFP and mCherry expressions were observed at 24, 48, and 72 h post-transfection. As a result, transfection efficiency achieved by using PEI in 293T cells is higher than in BHK-21 cells, which are ~90% and ~50%, respectively. Moreover, amongst four different transfection conditions, in both cell lines, 1 µg of plasmid DNA with a 1:3 DNA-PEI ratio yields the most efficiency with the least amount of toxicity. We used this condition for the syncytia observation in 293T cells as a model of the cell-to-cell transmission of SARS-CoV-2. Syncytia formation was successfully observed by detecting the giant cells expressing GFP/mCherry with multiple nuclei.